Francesco Filelfo e gli Jagelloni: un umanista italiano sulla scena europea - Costanza, Salvatore (Colloquia Litteraria, 2022)
Francesco Filelfo (Tolentino 1398- Florence 1481) was an Italian humanist who studied Greek in Padua, Venice and Constantinople, where he lived during his youth (1420-´27). He is known for his giant Collection of Latin and Greek Letters in 48 books. He also became acquainted with the most prominent personalities of philology, arts and politics at his time. Among them, we must count Władysław II Jagiełło (Vilnius 1362 - Gródek 1434), the granduke of Lithuania (1377-1434) and then king of Poland (since 1386). Filelfo encountered the old king in Buda at the Emperial Diet (1423), in which he took part as personal secretary of the Byzantine ruler John VIII Palaiologos. The Polish king was impressed by Filelfo´s unusual culture and brilliance so to invite him at his fourth marriage with Zofia Holsańska (ca. 1405-1461). The Italian humanist went to royal wedding held in Kraków, where he pronounced an official epitalamium, as he proudly writes to Władysław III Jagiełło born from this union. He sent this long letter to the young king of Poland just on the eve of the battle in Warna (1444), in which the latter heroically died fighting with Turks. Filelfos epistle to Władysław III influenced Polish humanists such as Albertus Brucius and Jan Ursyn. It is interesting to remark the role that Filelfo assigned to Polish nation as defender of Freedom against Ottoman expansion into Europe.